At My Best 4-5-6: Users’ observations of a health education curriculum-support resource - Robinson, Daniel B.; Gleddie, Douglas L.; Berg, Stephen (Alberta Journal of Educational Research, 2017)
Background and context: At My Best 4-5-6 is a curriculum-support resource intended primarily for elementary generalist or physical and health education specialist teachers in Canada. Created by Physical and Health Education Canada and AstraZeneca, At My Best 4-5-6 aims to educate students about—and encourage healthy behaviours related to—physical activity, healthy eating, and emotional wellness. Objective: At My Best 4-5-6 is a relatively new program that is now being subject to a pilot-revision-pilot process. Given the lack of research literature focused upon the first iteration’s implementation, the objective was to complete an investigation of teachers’ observations related to the resource. Method: A cross-sectional survey design utilized both quantitative and qualitative data collected through on-line surveys. The data gleaned from 66 survey questions were analysed to explore program implementation and effectiveness, as well as overall teacher opinions regarding At My Best 4-5-6. Results and conclusion: We share results focused upon the following: 1) demographics: users, locations, schools, and usage, 2) need for and suitability of At My Best 4-5-6, 3) implementation, and 4) cultural relevance. Given these results, we offer some discussion and concluding observations related to present and future versions of At My Best 4-5-6. Moreover, we suggest such concluding observations might be of particular interest to others engaged in the creation, dissemination, and/or research of similar health education curriculum-support resources. Historique et contexte: À mon meilleur 4-5-6 est une ressource conçue comme soutien au programme d’études à l’élémentaire et visant surtout les enseignants généralistes ou les enseignants spécialistes en éducation physique ou en éducation à la santé au Canada. Créé par Éducation physique et santé Canada et AstraZeneca, À mon meilleur 4-5-6 a pour objectif de conscientiser les élèves quant à l’activité physique, une saine alimentation et le bienêtre émotionnel. Objectif : À mon meilleur 4-5-6 est un programme relativement récent qui fait maintenant l’objet d’un processus d’essai de modification. Compte tenu du manque de documents de recherche portant sur la mise en œuvre de la première version du programme, notre objectif était d’enquêter sur les observations des enseignants relatives à la ressource. Méthode: Une étude transversale a porté sur des données quantitatives et qualitatives provenant d’enquêtes enligne. Les données tirées de 66 questions d’enquête ont servi dans l’analyse de la mise en œuvre et l’efficacité du programme, ainsi que les opinions globales qu’ont les enseignants de cette ressource. Résultats et conclusion : Nos conclusions portent sur les quatre points suivants : 1) des données démographiques : usagers, emplacements, écoles et usage, 2) la nécessité et la pertinence de À mon meilleur 4-5-6, 3) la mise en œuvre, et 4) la pertinence culturelle. En nous appuyant sur ces résultats, nous offrons des éléments de discussion et des observations finales en lien avec les versions actuelle et future de À mon meilleur 4-5-6. Nous proposons, de plus, que de telles observations finales pourraient intéresser tout particulièrement les personnes impliquées dans la création, la diffusion ou la recherche de telles ressources conçues comme soutien au programme d’éducation à la santé.